Barefoot running survey: Evidence from the field - David Hryvniak; Jay Dicharry; Robert Wilder (Journal of Sport and Health Science, 2014)
Background: Running is becoming an increasingly popular activity among Americans with over 50 million participants. Running shoe research and technology has continued to advance with no decrease in overall running injury rates. A growing group of runners are making the choice to try the minimal or barefoot running styles of the pre-modern running shoe era. There is some evidence of decreased forces and torques on the lower extremities with barefoot running, but no clear data regarding how this corresponds with injuries. The purpose of this survey study was to examine factors related to performance and injury in runners who have tried barefoot running. Methods: The University of Virginia Center for Endurance Sport created a 10-question survey regarding barefoot running that was posted on a variety of running blogs and Facebook pages. Percentages were calculated for each question across all surveys. Five hundred and nine participants responded with over 93% of them incorporating some type of barefoot running into their weekly mileage. Results: A majority of the participants (53%) viewed barefoot running as a training tool to improve specific aspects of their running. However, close to half (46%) viewed barefoot training as a viable alternative to shoes for logging their miles. A large portion of runners initially tried barefoot running due to the promise of improved efficiency (60%), an attempt to get past injury (53%) and/or the recent media hype around the practice (52%). A large majority (68%) of runners participating in the study experienced no new injuries after starting barefoot running. In fact, most respondents (69%) actually had their previous injuries go away after starting barefoot running. Runners responded that their previous knee (46%), foot (19%), ankle (17%), hip (14%), and low back (14%) injuries all proceeded to improve after starting barefoot running. Conclusion: Prior studies have found that barefoot running often changes biomechanics compared to shod running with a hypothesized relationship of decreased injuries. This paper reports the result of a survey of 509 runners. The results suggest that a large percentage of this sample of runners experienced benefits or no serious harm from transitioning to barefoot or minimal shoe running.